(untitled) (TAMADDUN NURI JURNALI, 2024)
The article examines the problem of literary influence through the prism of formal stylistic analysis, examines the influence of the work of Mikhail Sholokhov, as well as world literature on the progress of Uzbek literature of the 20th century, using the example of style, genre and form, as well as genre-compositional integrity.